The novel HLA‐C*03:605 allele, identified using next‐generation sequencing in a Chinese individual. (25th November 2022) - Liu, Keyao; Wang, Yan; Ma, Junxia; Wang, Linlin; Zhang, Qian
Abstract : The HLA‐C*03:605 allele differs from HLA‐C*03:04:01:01 by a single nucleotide in exon 4, position 680.